Analyzing the Relationship Between Current Ratio and DER - gea, Fransiskus; Tiffani, Dona Arhitania; Purnamasari, Pupung; Dasman, Sunita (Talent: Journal of Economics and Business, 2024)
This study aims to examine the effect of Current Ratio and Total Asset Turnover ratio on Solvency ratio, namely Debt to Equity ratio for the period 2011-2021. This research method is descriptive quantitative by conducting classical assumption tests, hypothesis testing, multiple linear regression analysis and coefficient of determination analysis using the SPSS version 26 application. The results of this study are partially, Current Ratio (CR) has no significant effect on Debt to Equity Ratio (DER) at PT Indofood Sukses Makmur, Tbk for the period 2011-2021. Total Asset Turnover (TATO) has a significant effect on Debt to Equity Ratio (DER) at PT. Indofood Sukses Makmur, Tbk for the period 2011-2020. Simultaneously Current Ratio and Total Asset Turnover (TATO) have a significant effect on Debt To Equity Ratio (DER) at PT. Indofood Sukses Makmur, Tbk for the period 2011-2021. The Coefficient of Determination as measured by the Adjusted R Square value is 0.576 or 57.6%, so that the contribution of Current Ratio and Total Asset Turnover is 57.6% to the Debt to Equity Ratio, while the remaining 42.4% is influenced by other variables not examined in this study.